Narration as reconciliation in The brothers, by Milton Hatoum - Souza, Mariana Jantsch (2014)
This article presents a reading of the novel The Brothers, by Milton Hatoum, as it highlights the role of narration as a factor of consolidation of an identity from the resignification of the past. To do so, the identity is approached with an eminently discursive process tied to the memory, because it finds in the past one of its constitutive sources. The way to appease the conflicts of the past is the writing, the narration, because it is the anguish of not knowing anything about himself and, therefore, being unable to shape an identity that drives Nael, the central narrator, to revolve the past. Throughout this memorial-narrative journey, the double issue tied to the identity formation problem emerges, highlighting how the relationship with alterity is reflected in the identity of the subject. The foregoing analysis finds theoretical support in the works of Stuart Hall, Joel Candau, Beatriz Sarlo, Michel Pollak, Ana Maria Lisboa de Mello.